Open market operations: beyond the new consensus - Jan Toporowski (Bank of Finland, 2006)
The emergence of the New Consensus in monetary policy has been followed by a renewal of interest in central banks' operating procedures, and specifically in the role of open market operations. There is a general view that overnight interest rates are most effectively controlled by standing or discount window facilities, rather than open market operations, and this view will probably now extend also to lender-of-last-resort intervention.The paper argues that this reduced role for open market operations is only in the context of controlling overnight rates of interest.In spite of the emphasis on control of overnight interest rates, medium and long-term interest rates remain the crucial instruments in the monetary transmission mechanism.Longer-term interest rates are susceptible to influence by open market operations, and their importance grows with financial development.
URN:NBN:fi:bof-20140807504
Keywords: E52; E58; 330; central banks; monetary policy; open market operations